Family Conflict, Mood, and Adolescents’ Daily School Problems: Moderating Roles of Internalizing and Externalizing Symptoms - Timmons, Adela C. (Child Dev, 2014)
Using daily diary data, this study examined cross-day associations between family conflict and school problems and tested mediating effects of daily negative mood and moderating effects of psychological symptoms. For 2 weeks, parents and adolescents (N = 106; mean age = 15.4) reported daily conflict; adolescents reported daily negative mood and school problems. Results indicated bidirectional, multi-day spillover between parent-adolescent conflict and school problems with daily negative mood statistically accounting for spillover both within and across days. Externalizing symptoms strengthened links between father-adolescent conflict and school problems, whereas depressive and anxious symptoms strengthened links between parent-adolescent conflict and daily negative mood. By demonstrating cross-domain transmission of daily problems, these findings highlight the salience of everyday events as possible intervention targets.